2012
DOI: 10.4028/www.scientific.net/amm.152-154.1215
|View full text |Cite
|
Sign up to set email alerts
|

6061 Aluminum Powder Making and its Thermal and Mechanical Properties

Abstract: Rapid solidification process was employed to make 6061 Al alloy powder. Powder size distribution was analyzed with SEM. Powder densities, i.e. apparent density and tap density, were measured. Thermal properties were measured via DSC. Surface condition and microstructures and their chemical compositions were characterized with XRD, OM, SEM/EDX. Nanoindentation was employed to obtain the hardness and Young’s modulus of the powders. The relationships among the atomization parameters, powder shapes and sizes, powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Fortunately, previous work by Chen et al reported indentation properties for gas-atomized Al 6061 at depths near 2565 µm in a soft epoxy and measured hardness values between 0.15 and 0.51 GPa [39], which is absolutely far too low for Al 6061 gas-atomized powder and therefore speaks to the limitation of Cao et al's model [8,37,40]. Regardless of the model proposed by [36] that aims to quantify an indentation depth limit, one could alternatively consider the plastic zone radius for a given indentation load and can be defined according to continuum mechanics [41], such that Equation ( 13) is given as…”
Section: On Comparing Indentation Hardnessesmentioning
confidence: 99%
“…Fortunately, previous work by Chen et al reported indentation properties for gas-atomized Al 6061 at depths near 2565 µm in a soft epoxy and measured hardness values between 0.15 and 0.51 GPa [39], which is absolutely far too low for Al 6061 gas-atomized powder and therefore speaks to the limitation of Cao et al's model [8,37,40]. Regardless of the model proposed by [36] that aims to quantify an indentation depth limit, one could alternatively consider the plastic zone radius for a given indentation load and can be defined according to continuum mechanics [41], such that Equation ( 13) is given as…”
Section: On Comparing Indentation Hardnessesmentioning
confidence: 99%